Difusão clássica em cadeias lineares com exclusão de volume e resetting utilizando as técnicas do espaço de Fock - Macedo, Enoque Ferreira (2025)
The effects of resetting in random search processes include backwardness in process completion, asymmetries in the diffusion process, overcrowding, and the origin of the optimization problem of first-pass time moments in stochastic physical systems. Besides, the exploration of resetting in stochastic dynamics has the ability to model human and animal search behavior, robotic explorations that depend on resetting strategies, protein searches on DNA, among others. In this context, we will make use of the Fock space formalism, which allows us to use second quantization operators adapted to the classical scenario with the aim of including the resetting process into classical diffusion in linear chains with volume exclusion. From this point, we explore a series of physical implications resulting from this inclusion, as well as the creation of optimization strategies.